The impact of social media in learning EFL iraqi Learners’ New words - Nesrallah, Omar; Murad Zangana, Ibtihal (Opción, 2019)
The study aims a to investigate the impact of social media in improving stu- dents’ ability of English language namely t vocabulary to acquisition a with second year EFL students in University of Diyala’’. Social media technolo- gies take on many different a forms including magazines, Internet forums, weblogs, social blogs, wikis, social networks, podcasts, pictures, videos etc’’. Technologies an cover blogging, picture-sharing, wall-posting, music-sharing just to name a few’’. Nowadays a Facebook technology seems to play an im- portant part for the social life of so many becoming more and more popular as a main means of communication, that it could also meet an educational need. ‘’a Thus, it could play a distinguished a role in foreign language learning and teaching’’. ‘’Several studies investigate using different technologies in learn- ing and teaching, in particular, foreign language learning’’. ‘’Still, rare stud- ies were interested an precisely in the role of social media in learning foreign languages’’. In this study was intended to a assess the role and effectiveness of social media use in to vocabulary learning